Uncommon presentation of Pityriasis versicolor; hyper and hypopigmentation in a same patient with variable treatment response - Riti Acharya; Madhu Gyawalee (Our Dermatology Online, 2017)
Pityriasis versicolor (PV) is a superficial fungal infection of skin caused by yeast Malassezia. Typical lesions are multiple small, round macules that coalesce to form confluent lesions. Eruption varies in color from patient to patient, but each person's lesions are usually of a single hue. Here we present a combination of both hypo and hyperpigmentated lesions of PV in a single patient. On treating the patient for 4 weeks with antifungals, complete clearance of hyperpigmented lesions were seen whereas hypopigmented ones became more accentuated.